Quantitative volumetric computed tomography embolic analysis, the Qanadli score, biomarkers, and clinical prognosis in patients with acute pulmonary embolism - Wei-Ming Huang; Wen-Jui Wu; Sheng-Hsiung Yang; Kuo-Tzu Sung; Ta-Chuan Hung; Chung-Lieh Hung; Chun-Ho Yun (Scientific Reports, 2022)
Abstract Detailed descriptions of acute pulmonary emboli (PE) morphology, total embolic volume (TEV), and their effects upon patients’ clinical presentation and prognosis remain largely unexplored. We studied 201 subjects with acute PE to the emergency department of a single medical center from April 2009 to December 2014. Patient hemodynamics, Troponin I and D-dimer levels, echocardiography, and the 30-day, 90-day and long-term mortality were obtained. Contrast-enhanced computed tomography (CT) of pulmonary structures and 3-dimensional measures of embolic burden were performed. The results showed a linear association between the greater TEV and each of the following 4 variables (increasing incidence of right ventricular (RV) dysfunction, higher systolic pulmonary artery pressure (sPAP), greater RV diameter, and RV/left ventricular (LV) ratio (all p < 0.001)). Among the measures of CT and echocardiography, TEV and RV/LV ratio were significantly associated with impending shock. In backward stepwise logistic regression, TEV, age and respiratory rate remained independent associated with impending shock (OR: 1.58, 1.03, 1.18, respectively and all p < 0.005).Total embolic burden assessed by CT-based quantification serves as a useful index for stressed cardiopulmonary circulation condition and can provide insights into RV dysfunction and the prediction of impending shock.